PELATIHAN DASAR PEMROGRAMAN VISUAL DI SMK AL-IHSAN BATUJAJAR: Visual Programming Basic Training at SMK Al-Ihsan Batujajar - Shandy Tresnawati; Nia Ekawati; Novita Lestari Anggreini (ASOSIASI IDEBAHASA KEPRI, 2023)
The purpose of this community service is to teach basic training on visual basic programming. Visual Basic programming is a programming language studied by Informatics Engineering and Computer Engineering students. Visual basic is a computer programming language that is directive or commands that can be understood by the computer to carry out certain commands. Community service carried out by TEDC Bandung Polytechnic students held training for students of SMK Al-Ihsan Batujajar on Basic Visual Basic Programming. This is related to the subjects available at the school, namely Windows-based Programming Subjects. The method implemented by TEDC Polytechnic students is community service in the form of training. The result of this community service is that students of SMK Al-Ihsan Batujajar can understand and implement the results of training in Windows-based Programming subjects. The conclusion of this community service is that students are able to understand and re-implement the material that has been taught by using existing facilities.